Association between Motivation and Dietary Adherence in Patients with Type 2 Diabetes Mellitus - Putri, Helmalia; Munir, Nur Wahyuni; Safruddin (Bantayang Omni Cendekia, 2025)
Background: Type 2 diabetes mellitus (T2DM) requires long-term dietary management to achieve optimal glycemic control and prevent complications. However, dietary adherence among patients with type 2 diabetes mellitus remains low. Motivation is an important factor that may influence patients’ adherence to dietary recommendations. Therefore, understanding the association between motivation and dietary adherence is essential to support the development of effective interventions aimed at improving diabetes management and patient health outcomes. Objective: This study aimed to analyze the association between motivation and dietary adherence of type 2 diabetes mellitus patients. Methods: This study employed a cross-sectional approach. Lemeshow formula was used to determine the sample size.Sociodemographic questionnaire, Treatment Self-Regulation Questionnaire (TSRQ), and dietary adherence questionnaire were utilized in this study. The Chi-Square test was employed to analyze the correlation between motivation and dietary adherence of patients with type 2 diabetes mellitus. Results: Of 67 respondents, majority of respondents had low dietary adherence, accounting for 43 respondents (64.2%) and over half respondents had good motivation, comprising 38 respondents (56.7%). Based on the Chi Square test, there was a significant association between motivation and dietary adherence in patients with type 2 diabetes mellitus, with a p-value of 0.002. Conclusion: Motivation is associated with dietary adherence of patients with type 2 diabetes mellitus. Therefore, health professionals, especially nurses, should provide continuous motivational support and patient-centered education to encourage dietary adherence among patients with type 2 diabetes mellitus.